IMPLEMENTATION OF PROJECT BASED LEARNING TO IMPROVE ABILITY TO DEVELOP LEARNING STRATEGIES ICT BASED - Hidayat, Rachmad; Suharsono, Naswan; Hari, Mohammad; Martha, Jefry Aulia; Mala, Iva Khoiril; Pratiwi, Titania Putri; Imania, Ekklesia (Nusantara Economics and Entrepreneurships Journals, 2024)
The emergence of a group of professional teachers in the field of ICT-based business education can be a driver for the birth of a group of young people who are market players for goods and services in the local, regional, national and global economy in the future. However, what learning strategies can be used and how to implement them in higher education is one of the efforts that must be prioritized for its realization. This study was conducted to test the effect of project-based learning models to improve students' abilities in making business plan projects. The research design used was a pre-experiment on 105 students starting from an initial competency analysis, selection of exercises in group assignments, and project assignments, followed by providing treatment with the application of PjBL in real class situations, data collection, and analysis of results. Data on improving managerial abilities and business plan making skills were analyzed using one-way analysis of variance. The results showed that the application of project-based learning can improve the ability to make business plan projects at a significance level of 5%.